Bank Sampah Graha Sewaka Dharma sebagai Alternatif Pengelolaan Sampah Perkantoran di Kawasan Pemerintahan Kota Denpasar - Dwija, I Kadek Pande Maha; Widyani, Ida Ayu Putu Sri (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: This research provides an alternative strategy in waste management by educating employees through the Graha Sewaka Dharma (GSD) waste bank in the Denpasar City Govermance area in Lumintang which is integrated with the 4R principles. Research methods: This research uses qualitative methods with observation and documentation data collection. The researchers use SWOT analysis (strengths, weaknesses, opportunities and threats) so that it solutions or alternative policy strategies can be found in managing office waste at the GSD Waste Bank. Results and discussion: The presence of the GSD waste bank is able to provide education on sorting waste, raising awareness among employees about collecting waste in a timely manner. Apart from that, employees who hand over waste will receive additional income which can be used for shopping at the Dharma Wiguna Cooperation. Implications: The existence of the GSD waste bank which is integrated with education regarding 4R principles provides basic knowledge for employees to manage waste from its source, namely households and office areas, empowering employees to have knowledge and skills so they are able to sort organic and non-organic waste.